Imaging and manipulation of skyrmion lattice domains in Cu2OSeO3 - Zhang, S; Bauer, A; Berger, H; Pfleiderer, C; van der Laan, G; Hesjedal, T (American Institute of Physics, 2016)
Nanoscale chiral skyrmions in noncentrosymmetric helimagnets are promising binary state variables in highdensity, low-energy nonvolatile memory. Nevertheless, they normally appear in an ordered, single-domain lattice phase, which makes it difficult to write information unless they are spatially broken up into smaller units, each representing a bit. Thus, the formation and manipulation of skyrmion lattice domains is a prerequisite for memory applications. Here, using an imaging technique based on resonant magnetic x-ray diffraction, we demonstrate the mapping and manipulation of skyrmion lattice domains in Cu2OSeO3. The material is particularly interesting for applications owing to its insulating nature, allowing for electric fielddriven domain manipulation.